Allergic contact dermatitis by Boswellia carterii ointment in a deep 2nd degree burn wound: a case report - P. Badr; A.A. Mohammadi*; S. Daneshamouz; S. Afsharypuor; M. Ayaz (Iranian Society of Pharmacognosy, 2018)
Numerous scientific texts insist on safe topical application of specific herbal products like those containing Boswellia oleogumresin, but adverse effects arising during clinical trials of herbal medicines give the opportunity to clarify the blind spots in the area of drug safety. A 36-year-old woman without allergic background had two burn wounds because of hot oil. Her hand's wound was diagnosed a superficial 2nd degree while the wound of her thigh was a deep 2nd degree. She was enrolled in a single-blind randomized clinical trial. Having been recruited in the Boswellia group, she received the formulation on the 3rd, 5th, 7th, 9th, and 11th day after her injury. The wound of her hand was completely healed on the 13th day without showing any adverse reactions, but she was suffering from irritation and pruritus on her thigh. In our experience, complete healing of the patient's hand wound without any side effects proved safe usage of the product for superficial burns, but its application in deeper injuries like the one on her thigh demonstrated the higher probability of severe reactions.